Maize Grain Quality as Influenced by 46 Years' Continuous Application of Fertilizers, Farmyard Manure (FYM), and Lime in an Alfisol of North-western Himalayas. Issue 2 (19th January 2021) - Thakur, Anjali; Sharma, R. P.; Sankhyan, N. K.; Kumar, Rameshwar
ABSTRACT: An understanding of maize nutritional quality response to fertilization is important to counter the widespread nutritional deficiencies among humans; however, little work has been done in this context. This study aimed to evaluate the effect of continuous application of fertilizers, FYM, and lime on the quality and yield of maize ( Zea mays L.) in a 46-year long-term experiment in an acid Alfisol of Himachal Pradesh, India. The experiment consisted of 10 treatments and one control in three replications in a randomized block design. Results revealed that 100% NPK+FYM and 100% NPK+lime recorded 48% and 37% higher maize grain yield than 100% NPK, respectively. The highest starch (67.09%), reducing (1.13%), and non-reducing sugar content (0.59%) were recorded in 100% NPK+FYM and lowest in control. The omission of sulfur and potassium (100% NPK (-S) and 100% NP, respectively) recorded significantly lower crude protein, fat, and fiber content compared to the treatments where sulfur and potassium were applied along with nitrogen and phosphorus. The grain calcium and zinc content were recorded highest in 100% NPK+lime and 100% NPK+Zn, respectively, whereas phosphorus, magnesium, and iron content in 100% NPK+FYM and lowest in control. From the study, it can be concluded that higher crop yield and better nutritional quality can be achieved with a balanced application of NPK fertilizers along with FYM and lime.